Feasibility Study of Evening Gowns Through an Exploration of Layering Techniques - Talitha Zada Achmad; Irmayanti Irmayanti (Jurnal Penelitian Pendidikan, 2026)
This study aims to test the feasibility of an evening party dress design that explores layering techniques. This research applies a project-based design approach through the development of PPE (Planning, Production, and Evaluation). Product feasibility evaluation involved 3 expert panelists and 10 trained panelists using questionnaire instruments in the form of quantitative descriptive analysis sheets with percentages. The results of the due diligence showed that this evening party dress earned an overall average score of 95%, which placed it in the "Very Worthy" category. Specifically, this fashion was rated very good in terms of design (91%), size (92%), aesthetics (96%), sewing technique (96%), fashion performance (98%), and uniqueness (98%). The results of the feasibility test showed that the manipulation of the fabric through layering techniques combined with bridal satin and tulle succeeded in creating a voluminous and balanced silhouette of sea waves. This fashion work is proven to be not only visually and aesthetically superior, but also meets the quality standards of performance and construction of modern party fashion.